Beyond the Walls: The Importance of Community Contexts in Immigration Detention. (August 2019) - Ryo, Emily; Peacock, Ian
Immigration detention facilities are commonly assumed to be insulated microcosms that maintain their existence separate and apart from the surrounding communities. Yet detention facilities are not hermetically sealed institutions. Drawing on unique and comprehensive data pertaining to all individuals held in immigration detention in the United States in fiscal year 2015, this study explores for the first time the importance of community contexts in immigration detention. Our multivariable analyses show a significant relationship between the characteristics of communities in which the facilities are located and detention length for individuals who were released pending the completion of their removal proceedings. Specifically, we find that the presence of legal service providers and social support networks in the communities is associated with shorter detention length, controlling for a variety of individual characteristics and contextual factors. These findings highlight the need for research on the social ecology of immigration detention—research that moves beyond the walls of detention facilities to consider the broader legal, social, and political contexts of surrounding communities in investigating the nature and consequences of immigration detention.